Kehidupan Masyarakat Jawa Di Jorong Purwajaya, Kabupaten 50 Kota: Tinjauan Kehidupan Sosial Budaya Tahun 1964-2017 - Fanny Mayang Sari; Erniwati Erniwati (Jurusan Sejarah FIS UNP, 2020)
This article examines the Life of Javanese Communities in Jorong Purwajaya, Regency of 50 Cities in 1964-2017. Describes how the struggles of the transmigrants to establish Jorong Purwajaya and how the social and cultural life of the Javanese people who live together in one location with different ethnicities. This research method is qualitative. Data collection techniques are interviews, observation and documentation. Interviewing the oldest in Purwajaya and the Purwajaya community. Using in depth interview techniques in-depth interviews with interview guidelines. The results showed that the history of Jorong Purwajaya establishment from the transmigration process of Halaban tea plantation workers who lost their jobs and home due to the PRRI rebellion in 1958. Jorong Purwajaya being a transmigration location for Javanese people in Payakumbuh influenced the concentration of Javanese communities in one location causing Jorong Purwajaya synonymous with Javanese culture, although Purwajaya is not only inhabited by Javanese but there are also Minangkabau and Batak ethnicities. The dominance of the Javanese culture to be dominant in Purwajaya over other ethnic groups living in the same location.